Estimation and mapping of Arias intensity in Nepal: Insights from seismic analysis in the Kathmandu Valley - POUDYAL, Dibyashree; NORDIN, Norhaiza; ROSLAN, Siti Nur Aliaa (Contributions to Geophysics and Geodesy, 2025)
Kathmandu Valley, the capital of Nepal, is located in the seismically active Himalayan belt and has a history of devastating earthquakes causing substantial loss of life and property damage. This study employs Probabilistic Seismic Hazard Analysis (PSHA) using the Foulser-Piggott Attenuation (FPA) model and Travasarou et al. (2003) with R-CRISIS software to calculate Arias intensity in Kathmandu Valley. Historical and recent seismic data within a 500-km radius were analysed, and the earthquake catalogue was declustered and standardized using ZMAP software, a tool developed for the statistical analysis and visualization of earthquake catalogues. Additionally, a Digital Elevation Model (DEM) based topographic analysis was conducted to assess the impact of local topography on seismic site response providing insights into, slope, soil amplification factors, and shear wave velocity across the region. The results reveal Arias intensity values ranging from 0.225 to 0.241 m/s at 2% and 10% probability of exceedance corresponding to 475 and 2475 years, mapped using ArcGIS. The analysis revealed that southwestern Kathmandu and Lalitpur exhibit higher Arias intensity values, while intensity decreases gradually from southwest to northeast. The DEM analysis further revealed that areas with low slopes, particularly in central Kathmandu, have higher soil amplification factors, potentially amplifying seismic waves. The shear wave velocity distribution highlights lower values in sedimentary deposits, indicating increased seismic vulnerability. These findings emphasize the need for effective urban planning and disaster preparedness strategies to mitigate earthquake impacts in Kathmandu Valley.